Investigating the Growth of CH3NH3PbI3 Thin Films on RF‐Sputtered NiOx for Inverted Planar Perovskite Solar Cells: Effect of CH3NH3+ Halide Additives versus CH3NH3+ Halide Vapor Annealing. Issue 3 (20th December 2019) - Pant, Namrata; Kulkarni, Ashish; Yanagida, Masatoshi; Shirai, Yasuhiro; Miyasaka, Tsutomu; Miyano, Kenjiro
Abstract: Investigating the low efficiency issue of radio frequency‐sputtered nickel oxide (sp‐NiO x )‐based perovskite solar cells (PSCs) due to a limited understanding of the correlation between perovskite growth and sp‐NiO x on the optoelectronic properties and photovoltaic device performance is critical. Herein, the crystallization of methylammonium (MA) lead iodide (MAPbI3 ) thin film (obtained from stoichiometric precursor ratio) on sp‐NiO x is shown, resulting in appearance of residual PbI2 grains. This is in contrast to perovskite growth on solution‐processed NiO x . The amount of residual PbI2 is suppressed by 1) adding excess MACl/MAI additives and 2) annealing the perovskite film in MACl/MAI vapor atmosphere. Structural and morphological results reveal significant reduction in the amount of residual PbI2 and enhanced grain size for all the cases while photophysical measurements reveal mitigation of trap/defect sites (within the bulk and at the interfaces) only for MACl/MAI vapor annealing case. As a result, photovoltaic devices exhibit improved performance only for the vapor annealing case. These results elucidate the critical role of maintaining stoichiometric ratio in perovskite and its crystallization on sp‐NiO x by eliminating the associated defects (influenced by sp‐NiO x ) in rendering improved performance, which can be insightful to further enhance the performance of PSCs. Abstract : The present study reveals a strong influence of sputtered NiO x on the perovskite crystallization and the appearance of residual PbI2 grains resulting in low photovoltaic device performance. Among different methylammonium (MA + ) halide additives and vapor treatment (to improve the perovskite crystallization) only MA + halide vapor‐treated perovskite shows suppressed recombination, enhanced carrier lifetime, and device efficiency.